Design and development of an hybrid light commercial vehicle. (1st October 2017) - Millo, F.; Cubito, C.; Rolando, L.; Pautasso, E.; Servetto, E.
Abstract: Nowadays the powertrain hybridization represents one of the most promising solution for delivery companies to reduce the fuel expenditure and to meet the stringent requirements of low emissions urban zones. In the framework of the collaborative Italian Regional iDea (innovative Diesel engine applications) project, which aims to develop innovative technical solutions for a more sustainable mobility, this paper highlights the fuel economy potential along the NEDC (New European Driving Cycle) and WLTC (Worldwide harmonized Light duty Test Cycle) driving cycles of a Plug-in hybrid powertrain developed for a light duty delivery vehicle, showing possible improvements in terms of CO2 emission reductions of 23% and 11%, respectively. After this preliminary investigation on the hybridization benefits, which has been carried out through numerical simulations, and a brief description of the methodology used to size the hybrid powertrain main components, the article shortly presents the powertrain control strategy and the development process of the first prototype. Finally, the work focuses on the main results which have been achieved by the first vehicle prototype during an experimental campaign carried out on a chassis dynamometer. Highlights: Analysis of a new plug-in hybrid powertrain developed for a light duty delivery vehicle. Assessment of its performance through both numerical simulation and prototype tests. Possible improvements in terms of CO2 emission reductions up to 23% highlighted.